Glucocorticosteroids and the Risk of NAFLD in Inflammatory Bowel Disease - Sara Jarmakiewicz-Czaja; Aneta Sokal; Piotr Pardak; Rafał Filip (Canadian Journal of Gastroenterology and Hepatology)
Each year, the incidence of nonalcoholic fatty liver (NAFLD) disease increases. NAFLD is a chronic disease. One of the most common causes of NAFLD is an inadequate lifestyle, which is characterized by a lack or low physical activity and eating highly processed foods rich in saturated fat and salt and containing low amount of fiber. Moreover, disturbances in intestinal microbiome and the use of certain drugs may predispose to NAFLD. NAFLD is an increasingly described disease in patients with inflammatory bowel disease (IBD). Recent data also indicate a frequent coexistence of metabolic syndrome in this group of patients. Certain groups of drugs also increase the risk of developing inflammation, liver fibrosis, and cirrhosis. Particularly important in the development of NAFLD are steroids, which are used in the treatment of many diseases, for example, IBD. NAFLD is one of the most frequent parenteral manifestations of the disease in IBD patients. However, there is still insufficient information on what dose and exposure time of selected types of steroids may lead to the development of NAFLD. It is necessary to conduct further research in this direction. Therefore, patients with IBD should be constantly monitored for risk factors for the development of NAFLD.